2022
DOI: 10.1155/2022/7388864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Du Meridian Moxibustion Combined with Mild Moxibustion on Female Pelvic Floor Myofascial Pain Syndrome: A Retrospective Cohort Study

Abstract: Objective. This study aimed to investigate the efficacy and safety of moxibustion in the treatment of pelvic floor myofascial pain syndrome. Methods. A total of 80 women with pelvic floor myofascial pain syndrome (cold coagulation and blood stasis type) were included in this retrospective study and divided into a moxibustion group and a drug treatment group. Patients who received Celebrex oral analgesia, health education, and lifestyle improvement were included in the drug treatment group. The patients that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… 58 Additionally, the treatment of this disease with traditional Chinese medicine has been a hot research direction in recent years, and acupuncture has been proven to be effective and fast. In addition, 23 electroacupuncture, 59 moxibustion and 60 cupping can also be used to treat CPPS. Abdulaziz, Khadiga et al used neurogenic acupoint dry cupping therapy to treat chronic pelvic pain (CPP) and found that it had a significant improvement effect on women’s high-sensitive C-reactive protein (hs-CRP) levels, pain perception and intensity, and pelvic pain.…”
Section: Discussionmentioning
confidence: 99%
“… 58 Additionally, the treatment of this disease with traditional Chinese medicine has been a hot research direction in recent years, and acupuncture has been proven to be effective and fast. In addition, 23 electroacupuncture, 59 moxibustion and 60 cupping can also be used to treat CPPS. Abdulaziz, Khadiga et al used neurogenic acupoint dry cupping therapy to treat chronic pelvic pain (CPP) and found that it had a significant improvement effect on women’s high-sensitive C-reactive protein (hs-CRP) levels, pain perception and intensity, and pelvic pain.…”
Section: Discussionmentioning
confidence: 99%